2017
DOI: 10.1002/zoo.21353
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory enrichment and scent cue associative learning in captive birds of prey

Abstract: As the use of enrichment in zoos has become a standardized husbandry practice, the continued improvement of enrichment programs should be concomitant with empirical validation of those practices. The role of scent as enrichment remains an unexplored avenue for many bird species. We conducted a multi-phase experiment to introduce wrapped food packages and scent cuing to indicate food presence into the exhibits of several birds of prey species at the Bronx Zoo, New York City, to assess if scent can function as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Unlike species of New World vultures (Cathartidae) (Potier et al, 2019), Africa's vultures (Accipitridae) reportedly have no refined olfactory senses (Houston, 1985). However, closely related species are able to use olfaction during foraging (Gilbert & Chansocheat, 2006;Nelson Slater & Hauber, 2017;Potier, 2019), indicating that it might be possible for the African species too. Current consensus is that they locate food exclusively by sight (Martin, Portugal, & Murn, 2012;Mundy, Bunchart, Ledger, & Piper, 1992;Spiegel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike species of New World vultures (Cathartidae) (Potier et al, 2019), Africa's vultures (Accipitridae) reportedly have no refined olfactory senses (Houston, 1985). However, closely related species are able to use olfaction during foraging (Gilbert & Chansocheat, 2006;Nelson Slater & Hauber, 2017;Potier, 2019), indicating that it might be possible for the African species too. Current consensus is that they locate food exclusively by sight (Martin, Portugal, & Murn, 2012;Mundy, Bunchart, Ledger, & Piper, 1992;Spiegel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the olfactory bulbs in some raptors species, including Turkey vultures (Grigg et al 2017), are relatively large (Zelenitsky et al 2011), and functional olfactory genes have been found in these birds (Yang et al 2015; Zhan et al 2013). Nevertheless, evidence from behavioral experiments is still needed, even though a recent study showed that raptors from different species may be able to learn olfactory cues (Slater and Hauber 2017). However, as these authors grouped nine individuals from five species, they were not able to conclude which species used their sense of smell.…”
Section: Introductionmentioning
confidence: 99%
“…A higher concentration of volatiles could also be the mechanism by which preening with leaves is triggered. The ability to detect VOCs through olfaction (Amo et al, 2011;Krause & Caspers, 2012;Nelson Slater & Hauber, 2017) or taste (Berkhoudt, 1992;Niknafs & Roura, 2018) an important step in understanding how the behaviour of preening with this species' leaves is triggered in Darwin's finches at a proximate level. If Darwin's finches are able to detect the volatile compounds of P. galapageium leaves it seems plausible that they would also incorporate them into their nest as self-fumigation with medical plants may have beneficial effects on the health of the nestlings (reviewed in Gwinner, 2013).…”
Section: Total Preening Eventsmentioning
confidence: 99%